Mesenchymal stem cells of the bone marrow raise infectivity of Plasmodium falciparum gametocytes - Ragavan Varadharajan Suresh; Bingbing Deng; Yonas Gebremicale; Kyle Roche; Kazutoyo Miura; Carole Long (mBio, 2023)
ABSTRACTPlasmodium falciparum is a parasite that causes the deadly human disease, malaria, and exhibits a complex life cycle in human and mosquito hosts. In the sexual stages of the parasite, gametocytes mature in the human body and propagate malaria when they are picked up by mosquitoes to infect new hosts. Previous research has shown that gametocytes home to the bone marrow of the host, where they complete their maturation and alter the behavior of resident mesenchymal stem cells (MSCs). In this study, we investigated the alternate side of this host-pathogen interaction, whether MSCs could alter the behavior of gametocytes. Gametocytes were co-cultured with MSCs until maturity and subsequently fed to mosquitoes to measure the oocysts produced. Here, we report, for the first time, that MSCs co-culture significantly elevated oocyst numbers in the infected mosquito compared to conventional culture medium. This enhancement appeared to be most effective during the early stages of gametocyte development and was not replicated by other cell types. MSC co-culture also increased the infectivity of field isolated P. falciparum parasites. This effect was partially mediated by soluble factor(s) as conditioned medium harvested from MSCs could also partially raise infectivity of gametocytes to nearly half compared to MSC co-culture. Together, this study reveals novel host-pathogen interactions, where the human MSCs are elevating the infectivity of malaria gametocytes.IMPORTANCEWhile prior research has established that Plasmodium gametocytes sequester in the bone marrow and can influence resident stem cells, the question of why they would choose this compartment and these cells remained a mystery. This study, for the first time, shows that being in the presence of mesenchymal stem cells (MSCs) alters the biology of the P. falciparum parasite and makes it more infectious to mosquitoes, hinting at novel mechanisms in its life cycle. This method also facilitates mosquito infections with field isolated parasites, affording research teams new infection models with parasites, which are challenging to infect into mosquitos using conventional culture methods. Finally, our findings that MSC-conditioned medium can also raise infectivity open avenues of investigation into mechanisms involved but can also serve as a practical tool for researchers hoping to increase oocyst yields.